Differential Impact of Sex on Seasonal Changes in Mantle and Tentacle Phospholipids and Triacylglycerols in Sepia officinalis. Issue 2 (19th March 2019) - Tir, Meriam; El Cafsi, Imen; Ammar, Rym B.; Mejri, Hssan; Tlili, Nizar; El Cafsi, Mhamed
Abstract: The aim of the present work was to study the effect of season on phospholipids and triacylglycerols (TAG) of mantle and tentacles of female and male wild Sepia officinalis . The identified phospholipids were phosphatidylethanolamine (PtdEtn), phosphatidylcholine (PtdCho), phosphatidylserine (PtdSer), and phosphatidylinositol (PtdIns), and PtdEtn was the major fraction. Results showed apparent seasonal variation of phospholipid content, particularly with female samples. Fatty acid composition of phospholipid classes showed a differentiation much more in the proportions than in the diversity of fatty acids. Results showed that the major saturated fatty acids were 16:0 and 18:0, the major monounsaturated fatty acids were 18:1 and 20:l, and the major polyunsaturated fatty acids were docosahexaenoic acid (22:6n‐3) (DHA) and eicosapentaenoic acid (20:5n‐3) (EPA). The results relative to TAG demonstrated significant variations. Principal component analysis confirmed the seasonal and sexual effects. This study could be appropriate for the improvement of consistent monitoring of phospholipid and TAG accumulation in cephalopod, which might be important for both physiological studies and food industries.